(untitled) (Research, Society and Development, 2020)
The article highlights law 13,415 / 2017, the result of Provisional Measure 746/2016, which establishes the policy for "New High School Education" in Brazil, proposed arbitrarily by the government Temer (2016-2018). The objective of this study is to discuss, in the light of theoretical references, the curriculum conception conveyed by this policy, as well as to highlight the contradictions between what was proposed in the current PNE (2014-2014) for the last stage of Basic Education. In methodological terms, this is a theoretical study, based on a dialogue between researchers in the field theoretical: Apple (2003); Freire (2015); Frigotto (2017); Frigotto & Motta (2017); Vieira (2017); Sousa & Aragão (2018). It was considered that the policy for the "New High School" fiercely contributes to the advancement of the neoliberal perspective and the narrowing of the curriculum in this stage of education, moving against the propositions of the current PNE. We defend the conception of curriculum in a multicultural perspective in a continuous movement of meaning.